2018
DOI: 10.3389/fmicb.2018.01005
|View full text |Cite
|
Sign up to set email alerts
|

A Dispensable Chromosome Is Required for Virulence in the Hemibiotrophic Plant Pathogen Colletotrichum higginsianum

Abstract: The hemibiotrophic plant pathogen Colletotrichum higginsianum infects Brassicaceae and in combination with Arabidopsis thaliana, represents an important model system to investigate various ecologically important fungal pathogens and their infection strategies. After penetration of plant cells by appressoria, C. higginsianum establishes large biotrophic primary hyphae in the first infected cell. Shortly thereafter, a switch to necrotrophic growth occurs leading to the invasion of neighboring cells by secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 73 publications
(122 reference statements)
0
65
0
Order By: Relevance
“…Recently, Plaumann et al . () have identified two T‐DNA insertion C. higginsianum mutants, vir‐49 and vir‐51, defective in the passage from biotrophy to necrotrophy. Both mutants show attenuated virulence on the host Arabidopsis thaliana and lack chromosome 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Plaumann et al . () have identified two T‐DNA insertion C. higginsianum mutants, vir‐49 and vir‐51, defective in the passage from biotrophy to necrotrophy. Both mutants show attenuated virulence on the host Arabidopsis thaliana and lack chromosome 11.…”
Section: Resultsmentioning
confidence: 99%
“…It appears that Pep1 is unlikely to be associated with the difference in virulence between CT-30 and CT-21 isolates as the expression of the gene is biologically insignificant (CT-30/CT-21 at the biotrophic phase, 5.83 AE 0.41/6.59 AE 0.19 (log 2 fold AE SEM, P > 0.01); Table S17). Recently, Plaumann et al (2018) have identified two T-DNA insertion C. higginsianum mutants, vir-49 and vir-51, defective in the passage from biotrophy to necrotrophy. Both mutants show attenuated virulence on the host Arabidopsis thaliana and lack chromosome 11.…”
Section: Researchmentioning
confidence: 99%
“…This means that effectors often localise to ‘compartments’ in the genome distinct from conserved genes (Frantzeskakis et al ., ). In Phytophthora and powdery mildew, this is realised by the location of effectors in gene‐sparse regions (Raffaele et al ., ; Spanu et al ., ; Raffaele & Kamoun, ; Hacquard et al ., ); in for example Colletotrichum , Fusarium and Leptosphaeria , this is enabled by physiologically dispensible chromosomes (Balesdent et al ., ; Vlaardingerbroek et al ., ; Plaumann et al ., ), and in Neofusicoccum and Ustilago this is made possible by clustering of virulence factors (Lanver et al ., ; Massonnet et al ., ).…”
Section: Pathogens Maintain Effector Reservoirs That Are Crucial For mentioning
confidence: 98%
“…Tansley review New Phytologist 2019). In Phytophthora and powdery mildew, this is realised by the location of effectors in gene-sparse regions (Raffaele et al, 2010;Spanu et al, 2010;Raffaele & Kamoun, 2012;Hacquard et al, 2013); in for example Colletotrichum, Fusarium and Leptosphaeria, this is enabled by physiologically dispensible chromosomes (Balesdent et al, 2013;Vlaardingerbroek et al, 2016;Plaumann et al, 2018), and in Neofusicoccum and Ustilago this is made possible by clustering of virulence factors (Lanver et al, 2017;Massonnet et al, 2018). The aforementioned ways in which pathogens uncouple housekeeping and virulence functions should probably be viewed as an adaptation that compensates for the reduction of saprotrophic ability ultimately leading to obligate biotrophy, as they enable a more fine-tuned deployment of virulence factors.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, between C. higginsianum isolates IMI 349063 and MAFF 305635, chromosome 12 was more variable than chromosome 11 and the core chromosomes, which were at similar levels of conservation (Plaumann et al 2018). This species illustrates a case where a pathogenic supernumerary chromosome (chromosome 11) was less variable than a non-or less-pathogenic supernumerary chromosome (chromosome 12) between the isolates of RIP, with 936 (97.8%) of those changes involving A's or T's in the 5' end of contig 205.…”
Section: Colletotrichum Higginsianummentioning
confidence: 92%